2001
DOI: 10.1111/j.1475-6811.2001.tb00026.x
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and spousal caregiving

Abstract: A community sample of 362 married couples participated in a study of attachment and spousal caregiving, which combined qualitative and quantitative components. The qualitative component focused on actual experiences of caregiving, assessed by participants' semi‐structured accounts of a situation involving their role as caregiver for their spouse. Attachment styles and their underlying dimensions (comfort with closeness, anxiety over relationships) were related to the type of support provided, the coping strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 41 publications
(40 reference statements)
4
93
0
7
Order By: Relevance
“…Por outro lado, a estrutura da relação do casal pode influenciar a forma como os indivíduos lidam com a dependência, bem como percepcionam a sua saúde física, mental e emocional (Rolland, 1994;Feeney & Hohaus, 2001), uma vez que a instalação da dependência no seio familiar tem o potencial de afetar a relação marital por alterar frequentemente a estrutura familiar (Andrasik, Larsson, & Grazzi, 2002;Wheis et al, 2002;Wright, 2003). Assim, quando o cuidador tem um bom ajustamento conjugal, poderá ficar mais vulnerável ao impacto das alterações estruturais envolvidas com o cuidar e ao efeito negativo da depressão (stressor adicional) na sua qualidade de vida.…”
Section: Discussionunclassified
“…Por outro lado, a estrutura da relação do casal pode influenciar a forma como os indivíduos lidam com a dependência, bem como percepcionam a sua saúde física, mental e emocional (Rolland, 1994;Feeney & Hohaus, 2001), uma vez que a instalação da dependência no seio familiar tem o potencial de afetar a relação marital por alterar frequentemente a estrutura familiar (Andrasik, Larsson, & Grazzi, 2002;Wheis et al, 2002;Wright, 2003). Assim, quando o cuidador tem um bom ajustamento conjugal, poderá ficar mais vulnerável ao impacto das alterações estruturais envolvidas com o cuidar e ao efeito negativo da depressão (stressor adicional) na sua qualidade de vida.…”
Section: Discussionunclassified
“…Indeed, several studies have shown that each partner's attachment insecurities contribute to the other partner's construction of, and dissatisfaction with, their relationship (e.g., Brennan & Shaver, 1995;Collins & Read, 1990). These partner effects have been noted in studies using observational methods, diary keeping, and narrative accounts as well as self-report questionnaires (e.g., Collins & Feeney, 2000;Feeney, 2002;Feeney & Hohaus, 2001).…”
Section: Attachment Insecurities Ptsd and Stsmentioning
confidence: 99%
“…Students in reconstituted families (8%) chose whether to rate their biological or step-parent. Because internal consistencies for the ARSQ and RSQ subscales are quite low (Griffin & Bartholomew, 1994), for each parent, anxiety and avoidant attachment dimensions were obtained using Feeney and Hohaus' (2001) measurement model for the 30-item RSQ. In that study, six of the parallel RSQ items loaded on the anxiety dimension and seven parallel items loaded on the avoidance dimension.…”
Section: Attachmentmentioning
confidence: 99%